Flexural tensegrity of segmental beams. (13th May 2020) - Boni, Claudio; Silvestri, Marco; Royer-Carfagni, Gianni
Abstract : The term 'flexural tensegrity' applies to beam-like structures composed of segments in unilateral contact, whose integrity under flexion is provided by tendons (cables), tensioned and later anchored at the end segments. In addition to the cable tension, the constitutive response depends upon the shape of the contact surfaces between consecutive segments, identified by the corresponding pitch lines and constructed with a double couple of conjugate profiles, in order to achieve an internal constraint equivalent to a spring hinge. The response is non-local in type, because the cable elongation, and consequently the stiffness of the spring hinges, depends upon the rotations of all the segments, but this effect becomes negligible under moderate deflections. In this case, the structure can be approximated with an elastica in the continuum limit. Testing of prototypes, manufactured with a 3D printer, shows a very good agreement with the theoretical predictions for different designs of the spring hinges. The system, whose stiffness can be functionally graded and actively controlled, can be packaged when the cable is slack and deployed by pulling the cable at one extremity. It appears particularly suitable to build soft arms for robotics or deployable compliant booms for aerospace applications.